PENGARUH PRODUK BANK SYARIAH TERHADAP MINAT MENABUNG DENGAN PERSEPSI MASYARAKAT SEBAGAI VARIABEL MODERATING DI PATI - Rusdianto, Hutomo; Ibrahim, Chanafi (Prodi Ekonomi Syariah Pascasarjana IAIN Kudus, 2016)
This study aimed to know the products of Sharia Banks, especially in Kota Pati district toward the interest of saving money by using the public perception as moderating. This research used descriptive quantitative method with populations Islamic Banking (BRI Syariah, BNI Syariah, Mandiri Syariah, Bank Jateng Syariah, Bank Muamalat) in Kota Pati district. The samples were the people who made transactions in Syaria Conventional Banks totaling 100 respondents taken using quota sampling technique. Methods of data analysis used MRA (Moderating Regresion Analysis) test. The results of this study showed that the products of existing Islamic banks in microfinance particularly in Kota Pati distrcit has impacts on people. It proves that the products (savings) of microfinance have benefits for customers. While the public perception can be moderating variables because the public banks can give education to the society that their products are free from usury.